2013
DOI: 10.1002/nau.22438
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins in bladder function: What do we know and where do we go from here?

Abstract: Available data show that our knowledge of NTs has greatly increased in recent years and that some results may have future clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 128 publications
3
52
0
5
Order By: Relevance
“…Given the known density of sensory afferents in the bladder, we hypothesized that a common pathway of stress expression may involve urinary solutes. Catecholamines (byproducts of cortisol metabolism) and neuropeptides including NGF and BDNF previously shown to be elevated in some patients with OAB were measured [31]. …”
Section: Methodsmentioning
confidence: 99%
“…Given the known density of sensory afferents in the bladder, we hypothesized that a common pathway of stress expression may involve urinary solutes. Catecholamines (byproducts of cortisol metabolism) and neuropeptides including NGF and BDNF previously shown to be elevated in some patients with OAB were measured [31]. …”
Section: Methodsmentioning
confidence: 99%
“…Increased urinary NGF levels are associated with bladder inflammation associated with chemical irritation, detrusor overactivity, and BOO (37). The role of NGF in the neurotrophic effects associated with obstruction was first identified by Steers et al in 1991 (38).…”
Section: Biomarkersmentioning
confidence: 99%
“…Subsequent studies have revealed that NGF is a target-derived trophic factor that promotes neuronal innervation and axonal terminal branching during development and has roles in the maintenance of neural homeostasis in adult. In the visceral organs, NGF and its receptor TrkA are found for their expression in neuronal and non-neuronal structures of the gut (Lin et al, 2005; Barada et al, 2007; Stanzel et al, 2008; Qiao and Grider, 2010), and NGF and TrkA are also expressed by the urinary bladder epithelial cells and detrusor muscle (see review (Cruz, 2014)). Pancreatic β cells are able to synthesize and secrete NGF (Rosenbaum et al, 1998) which can lead to selective hyperinnervation of the islets when NGF is overexpressed (Edwards et al, 1989).…”
Section: Neurotrophin Signaling In the Visceramentioning
confidence: 99%
“…BDNF is also found to express in non-neuronal tissues such as gut mucosa, adipocytes, liver, lung, pancreas and the urinary bladder (Lommatzsch et al, 1999; Bonini et al, 2001; Lucini et al, 2003; Lommatzsch et al, 2005; Grider et al, 2006; Steinkamp et al, 2012; Yu et al, 2012; Cruz, 2014). Its role in peripheral tissues is less studied.…”
Section: Neurotrophin Signaling In the Visceramentioning
confidence: 99%